SPIR Learning Agenda: Challenges for livelihoods and food security during the COVID-19 pandemic - Mulford, Michael; Gilligan, Daniel O.; Hidrobo, Melissa; Leight, Jessica; Alderman, Harold (2020)
Michael Mulford, Daniel Gilligan, Melissa Hidrobo, Jessica Leight, Harold Alderman, SPIR Learning Agenda: Challenges for livelihoods and food security during the COVID-19 pandemic JUL 30, 2020 - 09:00 AM TO 10:00 AM EDT